Provinces of British Columbia and Vancouver Island; with portions of the United States and Hudson's Bay Territories - http://id.worldcat.org/fast/160807 (John Arrowsmith., 1859)
1 item extracted from CO 60/4 (folio 497). 'The Provinces of British Columbia & Vancouver Island, with Portions of the United States & Hudson's Bay Territories.